OPTIMALISASI PERAN KODIM 0723/KLATEN DALAM PENANGGULANGAN BENCANA ERUPSI GUNUNG MERAPI TAHUN 2010 DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (STUDI DI DESA BALERANTE, KECAMATAN KEMALANG, KABUPATEN KLATEN, PROVINSI JAWA TENGAH) - , HARIAWAN; , Prof. Dr. H.A. Sudibyakto, MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed to find out the role of Kodim 0723/Klaten in coping with Mount Merapi eruption disaster in 2010 in Balerante Village and the constraints encountered. It also aimed to find out the measures taken to optimize the role of Kodim 0723/Klaten and their implication to regional resilience. This study was a descriptive qualitative research with interview, observation, and library study as techniques of collecting data. Technique of analyzing data used was descriptive qualitative one analyzing and describing systematically the measures of optimizing the role of Kodim 0723/Klaten in coping with Mount Merapi eruption disaster in 2010 in Balerante Village and their implication to regional resilience. The research was taken place in Kodim 0723/Klaten (Military District Command 0723 of Klaten) and Balerante Village. The result of research showed that Kodim 0723/Klaten as District Command played a sufficiently important role in dealing with the Mount Merapi eruption disaster, despite less optimality. Three constraints were encountered: a. limited quality of human resource, b. some materials (equipments) the Kodim had not had yet in dealing disaster, c. The disaster management institution could not have accommodated and controlled the institutions/elements belonging to disaster management at that time. The measures of optimizing the role of Kodim 0723/Klaten in coping with Mount Merapi eruption disaster in 2010 included: a. human resource optimization, through education and training, b. material/equipment optimization, through requesting material support to superior unit, cooperation and coordination with related institution and effective use and maintenance, c. disaster management institution optimization, through utilizing BPBD (Local Disaster Management Agency) in improving alertness and coordination among the institutions. The implications generated affected social condition of society including the embedment of Pancasila values, the creation of democratic political stability, the recovery of economic activity, the organization of religious life, societal education and culture, and the creation of secure feeling and TNIâs integrity into society. Thus, these could improve the area tenacity pertaining to ideological, political, economic, social-cultural, and security defense aspects.